Distinct immunopathological mechanisms of EBV‐positive and EBV‐negative posttransplant lymphoproliferative disorders. Issue 8 (17th June 2021) - Nakid‐Cordero, Cecilia; Choquet, Sylvain; Gauthier, Nicolas; Balegroune, Noureddine; Tarantino, Nadine; Morel, Véronique; Arzouk, Nadia; Burrel, Sonia; Rousseau, Géraldine; Charlotte, Frédéric; Larsen, Martin; Vieillard, Vincent; et al.
Abstract : EBV‐positive and EBV‐negative posttransplant lymphoproliferative disorders (PTLDs) arise in different immunovirological contexts and might have distinct pathophysiologies. To examine this hypothesis, we conducted a multicentric prospective study with 56 EBV‐positive and 39 EBV‐negative PTLD patients of the K‐VIROGREF cohort, recruited at PTLD diagnosis and before treatment (2013–2019), and compared them to PTLD‐free Transplant Controls (TC, n = 21). We measured absolute lymphocyte counts ( n = 108), analyzed NK‐ and T cell phenotypes ( n = 49 and 94), and performed EBV‐specific functional assays ( n = 16 and 42) by multiparameter flow cytometry and ELISpot‐IFNγ assays ( n = 50). EBV‐negative PTLD patients, NK cells overexpressed Tim‐3; the 2‐year progression‐free survival (PFS) was poorer in patients with a CD4 lymphopenia (CD4 + <300 cells/mm 3, p < .001). EBV‐positive PTLD patients presented a profound NK‐cell lymphopenia (median = 60 cells/mm 3 ) and a high proportion of NK cells expressing PD‐1 (vs. TC, p = .029) and apoptosis markers (vs. TC, p < .001). EBV‐specific T cells of EBV‐positive PTLD patients circulated in low proportions, showed immune exhaustion ( p = .013 vs. TC) and poorly recognized the N‐terminal portion of EBNA‐3A viral protein. Altogether, this broad comparison of EBV‐positive and EBV‐negative PTLDs highlight distinct patterns of immunopathological mechanisms between these two diseases and provide new clues for immunotherapeutic strategies and PTLD prognosis. Abstract : This broad comparison of T cell and NK cell characteristics between EBV‐positive and EBV‐negative PTLDs highlight distinct patterns of immunopathological mechanisms and provide new clues for prospective surveillance and immunotherapeutic strategies.